2019
DOI: 10.3389/fsoc.2019.00005
|View full text |Cite
|
Sign up to set email alerts
|

Community Sport and the Politics of Aging: Co-design and Partnership Approaches to Understanding the Embodied Experiences of Low-Income Older People

Abstract: The promotion of physical activity for older people is dominated by biomedically informed polices emphasizing the prescription of exercise as medicine and a universal approach to the promotion of active aging in later life. Yet, more recent research recognizes that being physically active in later life is complex and contested, shaped by the intersections of biological, psychological, and sociological experiences, and requires differentiated responses that address this complexity. There is a disconnect between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Three of the most frequently identified barriers to taking up PA that are faced by individual patients are the perceived nature of their underlying health condition, 13,26,53,68–79 patients’ knowledge and understanding of the benefits of PA 13,18,22,26,30,42,53,68–72,76,77,80–86 and patients’ time/capacity 13,18,22,26,30,42,53,68,70–72,75,76,81,87–89 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the most frequently identified barriers to taking up PA that are faced by individual patients are the perceived nature of their underlying health condition, 13,26,53,68–79 patients’ knowledge and understanding of the benefits of PA 13,18,22,26,30,42,53,68–72,76,77,80–86 and patients’ time/capacity 13,18,22,26,30,42,53,68,70–72,75,76,81,87–89 …”
Section: Methodsmentioning
confidence: 99%
“…Although the majority of the included studies were within general populations, several looked at specific populations including people with type 2 diabetes mellitus, 13,78,81 the elderly 26,42,69,74,80,88 and patients with chronic pain and osteoarthritis 75,76 . Patients with pre‐existing conditions understandably cite underlying health concerns more frequently as a barrier to participation than those without.…”
Section: Methodsmentioning
confidence: 99%
“…Contemporary health and sport policy often promotes participation in sport and physical occupations as a universal panacea and solution to national inactivity problems (British Medical Association, 2014; Department for Culture Media and Sport, 2015; Hagell, 2016;Royal College of Psychiatrists, 2012a, 2012bSport England, 2016). However, literature has challenged these prevailing governance trends, which tend to be both responsibilising and individualistic (Mansfield et al, 2019;Smith & Perrier, 2014;Williams, 2017;Williams & Gibson, 2018) and construct participation in sport, exercise, and physical occupations within a biomedical frame; 'exercise as medicine'. This tendency fails to account for the complex social demands and risks participation entails (Pullen & Malcolm, 2018;Williams et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research with low SES groups has indicated that lack of time plays a role [19][20][21][22] together with a lack of enjoyment of physical activity [20], poor health [15], and being overweight or obese [23]. People who are inactive report that negative emotions driven by poor past experiences or fear, worry, and anxiety about their physical competency are barriers to physical activity [24], and people who are overweight or obese experience stigma trying to exercise leading to exercise avoidance [19,[25][26][27][28]. Thus, emotions play an important part and may influence whether inactive or overweight individuals undertake and maintain physical activity.…”
Section: Introductionmentioning
confidence: 99%